SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN TEKNISI TERBAIK PADA CV. PERDANA MITRA INOVASI MENGGUNAKAN METODE MOORA - Aldi Kurniawan; Ahmad Heru Mujianto; Tanhella Zein Vitadiar; Kristianto, Hery (Fakultas Teknologi Informasi, 2024)
Information technology is developing very rapidly, many companies face complex challenges in theiroperational management, including CV. Perdana Mitra Inovasi Jombang, an ISP (Internet Service Provider)that is a subnet of PT. Digital Media Telematika Lamongan. This company struggles with selecting the besttechnicians due to a manual selection process that is highly subjective. Network reliability and servicequality, which depend on the technicians' skills, are key to maintaining customer satisfaction andcompetitiveness in the market. Therefore, a system that utilizes information technology is needed to enhanceobjectivity and consistency in technician selection. The MOORA method was chosen to develop this systembecause it effectively addresses multi-criteria problems by considering various relevant factors. MOORAallows for the evaluation of alternatives based on established criteria and assigns weights according to theirimportance, such as attendance, discipline, skills, teamwork, and attitude. With this implementation of themethod, the company is expected to optimize the process of selecting the best technicians, provide monthlyperformance rewards, and motivate technicians to contribute significantly. This system is anticipated topositively contribute to the company by maintaining customer satisfaction and sustaining competitiveness inthe market.Keywords: Selection, Best Technician, Decision Support System, Moora.